Cancer immunotherapy - Naranjo-Vela , Tatiana Katherine (2023)
Immunotherapy as a treatment for cancer has developed considerably in recent years, proving to be a promising type of treatment against cancer. This therapy consists of the administration of substances produced by the body or through a laboratory, to help the immune system to accurately identify and eliminate neoplastic cells in the patient. The latest research proposes to improve the recognition of tumor antigens and to take advantage of the effector mechanisms of the individual's own immune cells; it also suggests directly stopping cancer cells, since they stimulate the immune system's capacity to recognize them by activating defense mechanisms that prevent cancer proliferation. However, it remains a challenge to increase effectiveness, specifcity and safety, as this type of treatment is not without limitations and adverse effects. Among the types of immunotherapy currently available are: administration of cytokines, vaccines, viruses, monoclonal antibodies, checkpoint inhibitors, and TIL and CAR-T cell therapy, all of which have as their main function to modulate the immune response. In the present literature review, important aspects of enhancing antitumor immunity and suppressing the mechanisms of immunosurveillance evasion, with their relationship to immunotherapy, will be presented.